(untitled) (Cadernos de Literatura em Tradução, 2021)
The aim of this work is to discuss the process of translating the poems “Will and Testament for Aarya Tara” and “Yuthok Lane” by Tenzin Dickie, a poet from Tibet. Some aspects that have driven this work are: the equation of phonological and semantic aspects, without significant displacements in the field of significance, and cultural translation as negotiation between cultural values.